A Comparative Review on Microbiota Manipulation: Lessons From Fish, Plants, Livestock, and Human Research - Brugman, Sylvia; Ikeda-Ohtsubo, Wakako; Braber, Saskia; Folkerts, Gert; Pieterse, Corné M. J.; Bakker, Peter A. H. M. (Frontiers in Nutrition, 2018)
During recent years the impact of microbial communities on the health of their host (being plants, fish and terrestrial animals including humans) has received increasing attention. The microbiota provides the host with nutrients, induces host immune development and metabolism and protects the host against invading pathogens (Backhed et al., 2005; Garrett et al., 2010; Dimitroglou et al., 2011; Berendsen et al., 2012; Pieterse et al., 2016; Andreote and Pereira, 2017). Through millions of years of co-evolution bacteria and hosts have developed intimate relationships. Microbial colonization shapes the host immune system that in turn can shape the microbial composition (Rawls et al., 2006; Brugman et al., 2014; Raaijmakers and Mazzola, 2016). However, with the large scale use of antibiotics in agriculture and human medicine over the last decades an increase of diseases associated with so-called dysbiosis has emerged. Dysbiosis refers to either a disturbed microbial composition (outgrowth of possible pathogenic species) or a disturbed interaction between bacteria and the host (Sommer et al., 2017). Instead of using more antibiotics to treat dysbiosis there is a need to develop alternative strategies to combat disturbed microbial control. To this end, we can learn from nature itself. For example, the plant root (or ‘rhizosphere’) microbiome of sugar beet contains several bacterial species that suppress the fungal root pathogen Rhizoctonia solani, an economically important fungal pathogen of this crop (Mendes et al., 2011). Likewise, commensal bacteria present on healthy human skin produce antimicrobial molecules that selectively kill skin pathogen Staphylococcus aureus. Interestingly, patients with atopic dermatitis (inflammation of the skin) lacked antimicrobial peptide secreting commensal skin bacteria (Nakatsuji et al., 2017). In this review, we will give an overview of microbial manipulation in fish, plants, and terrestrial animals including humans to uncover conserved mechanisms and learn how we might restore microbial balance increasing the resilience of the host species.